Initial destination hospital of paediatric prehospital patients in rural Victoria. (2nd March 2016) - Kloot, Kate; Salzman, Scott; Kilpatrick, Sue; Baker, Tim; Brumby, Susan A
Abstract: Objective: The objective of this present study was to describe the initial destination hospital of paediatric patients transported by Ambulance Victoria paramedics within the South Western area of Victoria to determine the proportion of patients that bypassed their closest hospital. Methods: All Ambulance Victoria primary ambulance transports for paediatric patients aged 1 month to 14 years in the Barwon South West region between 1 April 2008 and 28 February 2011 were reviewed. Each case was examined to determine the destination hospital location relative to the case scene location, and the overall nature of each case was grouped into one of seven categories (medical respiratory, medical cardiac, medical neurological, medical other, trauma time critical, and trauma non‐time critical). Results: There were 1191 cases identified, with 978 (82%) being taken to the closest hospital and 213 (18%) to a more distant facility. The average distance travelled from the scene to the destination hospital was 15.2 km, and almost 90% of patients transported to the nearest hospital were within 15 km of that hospital. Time critical trauma cases and respiratory‐related medical cases had higher rates of transport to more distant hospitals as their initial destination (26% to non‐closest and 23% to non‐closest, respectively). Conclusion: The patient's condition and their location relative to the larger medical facilities appear to influence the decision of destination hospital. Uncertainty regarding the availability of 24 h hospital services and staffing details may contribute to longer transfers.